Factors of delay in the detection and diagnosis of pulmonary tuberculosis in Croatia: A Qualitative study - Munko, Tatjana; Janev Holcer, Nataša (Nursing and Health Sciences Journal (NHSJ), 2025)
Delays in the detection, diagnosis and treatment of TB are an obstacle in the control of the disease and may be responsible for a longer period of infectivity at the population level. The objective of this study is to estimate the risk factors that contribute to the delays in TB detection attributed to both the patient and the health care system. The focus group method was applicable in the present study. Study subjects (patients and health care professionals) were divided into two basic groups. A total of 9 patients aged 18 to 76 and 4 health workers (epidemiologist, family physician / general practitioner, microbiology specialist and pulmonology specialist) participated in the focus groups. In more than half of the patients, a delay in diagnosis was observed. The patient delay time frame varied between 2 and 4 months. The reasons for the delayed reporting of TB symptoms to the doctor are the attribution of health problems to temporary medical conditions and, as stated by the respondents, their own stubbornness. Healthcare workers believe that the COVID-19 pandemic has had a negative impact on the recognition of tuberculosis to a certain extent, as all activities were primarily aimed at determining the COVID-19 status of patients with any type of respiratory symptoms. Raising awareness about the risk factors of delay in the detection of tuberculosis among risk groups, the general population and health care professionals will help prevent delays in treatment and further reduce the incidence of TB in the general population.